The effect of parental support on the quality of life of children with thalassemia - Wuri Utami; Mohd Nazri Mohd Daud; Khalid Mokti (Uphills Publishers LLC, 2024)
Introduction: Thalassaemia is a blood disorder that is passed down from parents to their children. Patients should receive blood transfusions regularly. Children with thalassaemia will undergo treatment for a long time. These extreme impacts cause various physical, emotional, social, and environmental disorders that can reduce the quality of life of people with persistent thalassaemia major. Objectives: This study aims to determine the effect of family support on the quality of life in children with thalassaemia major. Methods: This research is a type of quantitative correlation with the cross-sectional approach. The sample of all thalassemia patients in AprilAugust 2022 until 2024 Agustus, was 120 pediatric patients selected using the total sampling technique. Bivariate analysis using chi square. Results: The age characteristics of children with thalassaemia were 83 (69.2%), the majority of females were 65 (54.2%). Family support was mostly positive for 63 (52.5%) and the quality of life of children with thalassaemia was mostly for 64 respondents (65.8%) in the normal category. There is a relationship of family support for the quality of life of children with thalassaemia at the Dr. Soedirman Regional General Hospital, Kebumen. Conclusions: Support family and friends, as well as providing a adequate for parents is very important in improving the quality of life of children Thalassaemia.